BIODIVERSITY OF FISH PARASITES FROM GUANDU RIVER, SOUTHEASTERN BRAZIL: AN ECOLOGICAL APPROACH - de Azevedo, Rodney K. (2011)
Here, we performed a quantitative analysis of the parasite communities in 21 species of fish from Guandu River, Brazil; we evaluated the effects of some host traits (body size, social behavior, fish's habitat, trophic category and ability to migration) on the diversity of their communities of metazoan parasites. To measure quantitative diversity, we used parasite species richness, as well as the average taxonomic distinctness of the assemblage and its variance. The parasite species richness, the taxonomic distinctness and the variance were unaffected by the number of host individuals examined per species. Fish body length proved to be the main predictor of parasite species richness, although it did not correlate with parasite taxonomic distinctiveness. The mains host features associated with the taxonomic diversity of parasites were schooling behavior and omnivores trophic category. Parasite communities found in fish from Guandu River isolationist communities.